Reaching conceptual stability by re-articulating empirical and theoretical work on affordances - Malo, Roman; Prié, Yannick (Frontiers in Psychology, 2024)
Theoretical developments on affordances have multiplied, leading to a lack of stability for this concept and potential loss of scientific validity. Yet the concept should not be abandoned as it is at the heart of post-cognitive theories and reused in several fields of research. Empirical work could have helped reaching a consensus for these researchers, but it remains scarce, hardly catches up with theory, and cannot play its role in scientific development, as it lacks articulation with theoretical work. That is why re-articulating theoretical and empirical work on affordances seems a necessity in order to draw a more productive path for the concept to move further towards its promises. To achieve such a goal, we need to focus on empirical work. This can be done by considering recent theoretical proposals, and designing associated empirical methodologies. The requirements and the framework we are proposing constitute a step in this direction.